Metabolomics Analysis of Soybean Hypocotyls in Response to Phytophthora sojae Infection - Zhu, Longming; Zhou, Yang; Li, Xiangnan; Zhao, Jinming; Guo, Na; Xing, Han (Frontiers in Plant Science, 2018)
Soybean is one of the most important economic and oil crops across the world. Phytophthora root rot (PRR), caused by Phytophthora sojae (P. sojae), is a major disease in most soybean-growing regions worldwide. Here, we investigated metabolic changes in hypocotyls of two soybean lines, Nannong 10-1 (resistant line, R) and 06-070583 (susceptible line, S), at two time points (12 hpi and 36 hpi) after P. sojae infection and metabolic differences between the R line and the S line. In total, 90 differentially accumulated metabolites (DAMs) were identified after P. sojae infection; the levels of 50 metabolites differed between the R line and the S line. There are 28 DAMs that not only differentially accumulated between the R line and the S line but also differentially accumulated after P. sojae infection. Based on the changes of these DAMs in response to P. sojae infection in different lines and at different timepoints, and the differences in the contents of these DAMs between the R line and the S line, we speculated that DAMs, including sugars (monosaccharides and oligosaccharides), organic acids (oxalic acid, cumic acid), amino acid derivatives, and other secondary metabolites (mannitol, octanal, hypoxanthine and daidzein etc.) may participate in the metabolic-level defense response of soybean to P. sojae. In this study, an integrated pathway-level analysis of transcriptomics (obtained by RNA-Seq) and metabolomics data illustrated the poor connections and interdependencies between the metabolic and transcriptional responses of soybean to P. sojae infection. This work emphasizes the value of metabolomic studies of plant-pathogen interactions and paves the way for future research of critical metabolic determinants of the soybean-P. sojae interaction.